Membangun Pemahaman Keagamaan Siswa Melalui Pendekatan Konstruktivisme Dalam Pendidikan Agama Islam - Dian Valuvi; Muzaiyanah; Mudrikatu Ulya; Muhammad Coirul Rizki (PT. Nawa Edukasi Nusantara, 2025)
Education employs various methods to enhance students’ learning interest and way of thinking. However, conventional teaching methods, such as delivering material textually and using one-way lectures, often reduce students’ critical thinking abilities, making them passive, easily bored, and less motivated in learning. Therefore, this study aims to examine learning approaches that encourage students to actively analyze, explore, and engage in discussions. This research applies the constructivist approach, based on three main concepts: assimilation, accommodation, and equilibration. Through this approach, students construct their own understanding based on their learning experiences, making the learning process more meaningful. The study uses a literature review method and is expected to serve as a reference for Islamic Education (PAI) teachers in designing more active, student-centered learning, encouraging students to think critically and solve problems independently.